Profile of coordination motor abilities in elite judokas and badminton players compared to non-athletes - Jaworski, J.; Lech, G.; Ambrozy, T.; Zak, M. (Biomedical Human Kinetics, 2020)
Study aim: To determine the level and internal structure of profiles of coordination motor abilities in elite judokas and badminton players compared to a group of non-athletes.